Long-term rebleeding risk following endoscopic therapy of small-bowel vascular lesions with device-assisted enteroscopy. Issue 4 (April 2016) - Pinho, Rolando; Ponte, Ana; Rodrigues, Adélia; Pinto-Pais, Teresa; Fernandes, Carlos; Ribeiro, Iolanda; Silva, Joana; Rodrigues, Jaime; Mascarenhas-Saraiva, Miguel; Carvalho, João
Abstract : Background and aims: The effectiveness of endoscopic therapy of small-bowel vascular lesions (SBVL) remains unclear as recent studies report high recurrence rates after 2 years of follow-up. This study aimed to evaluate the long-term rebleeding risk after endoscopic therapy of SBVL and to identify predictive factors of rebleeding. Methods: This was a retrospective single-center series of patients with SBVL treated endoscopically between July 2007 and February 2015. Relevant data from patient files, capsule endoscopies, and enteroscopy reports were retrieved. The primary endpoint was long-term rebleeding and the secondary endpoints were risk factors for rebleeding and transfusion requirements. Results: Thirty-five patients were included. Capsule endoscopies indicated angioectasias in 74.3% and blood in the remaining; angioectasias were found in 97.1% of enteroscopies. Rebleeding occurred in 40% of patients during a median follow-up of 23 months (interquartile range 9–43). The rebleeding rate at 1, 2, 3, 4, and 5 years was 32.7, 38.3, 46.0, 53.7, and 63.0%, respectively. Only the presence of high-risk comorbidities (aortic valve stenosis, chronic renal or liver disease, or Osler–Weber–Rendu syndrome) was associated with higher rebleeding ( P =0.006) in the univariate and multivariate analyses, being 51.3%/67.6% at 1/3 years, compared with 6.7%/22.2% in patients without any of these comorbidities. Transfusion requirements decreased to 6.3 (0.0–6.0) packed red blood cells units the year after endoscopic therapy compared with 11.5 (2.0–17.0) in the previous year ( P =0.002). Conclusion: More than half of the patients had rebleeding after 5 years of follow-up, although transfusion requirements decreased. Patients with high-risk comorbidities are more likely to rebleed.